Cryopreservation of ovules and somatic embryos of citrus using the encapsulation-dehydration technique - Gonzalez-Arnao, Maria Teresa; Juárez, José; Ortega, Carmen; Navarro, Luis; Durán-Vila, Núria (2017)
Cryopreservation of ovules and somatic embryos from several genotypes of citrus was achieved using the encapsulation-dehydration technique. Survival of cryopreserved ovules was occasional and erratic after different pregrowth conditions in liquid medium with 0.75M, 1M or up to 1.25M sucrose. An efficient cryopreservation protocol was established for somatic embryos derived from two embryogenic sources (ovules and cut thin layer explants from stigma, style and ovaries). High survival rates (75-100%) were consistently obtained after 1 day pregrowth in 0.75M sucrose, desiccation down to 20-25% moisture content in the beads and direct immersion in liquid nitrogen. The histological study showed that embryos subjected to the encapsulation-dehydration, accumulated high sucrose levels which appear to ensure the recovery of the whole embryo after cryopreservation.